Topological socio-cultural evolution a predictor of ethnic conflicts in multi-ethnic societies - Muthusamy, Paramasivam; Wickramasinghe, Chaminda Nalaka; Shanmuganathan, Thilagavathi (Universiti Putra Malaysia Press, 2014)
Ethnic conflicts have been one of the biggest single threats for the progress of collaborative human societies. Ethnic issues are common to most multi-ethnic societies. Some of the conflicts are violent and damaging but not all are negative. Owing to the rapid growth of ethnic problems, attempts have been made to overcome them across many nations despite the change in governments or government policies in recent years. However, so far none of the discussions and solutions is able to explain the influence of socio-cultural evolution on the changes in ethnic identities in multi-ethnic society and the effect on the minority. Further, attention is given to discuss the impact of socio-cultural formation topologies of multi-ethnic societies on ethnic issues. In this concept paper, authors explain the socio-cultural evolution process of multi-ethnic societies and the impact of ethnic topologies on ethnic conflicts.